Tinjauan Aspek Ergonomi Pada Ruang Penyimpanan Berdasarkan Standart Nasional Akreditasi Rumah Sakit (SNARS) Edisi 1 Di RSU Tere Margareth Medan Tahun 2020 - Esraida Simanjuntak; Ermas Estiyana; Septi Anastasya (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2022)
In SNARS edition 1, it is known that medical record documents in paper or electronic form must be kept safe and confidential so they must be stored in a location that is protected from water, fire, heat, and other damage and protected from interference with access and unauthorized use. The purpose of this study was to determine the ergonomics aspect based on the National Standard for Hospital Accreditation (SNARS) Edition 1. The method used was observation and interviews with a descriptive type of research located at Tere Margareth General Hospital Medan in July 2020. The population in this study was the physical aspect. Ergonomics and medical records officers in the storage room as many as 2 people using the total sampling technique. is the storage room for medical record files at the Tere Margareth hospital that does not meet accreditation standards because there are still problems that occur related to room security which can be assessed based on the standard of ergonomic aspects. Ask the hospital to pay more attention to the state of the medical record storage room in order to meet the standard assessment elements of information management and medical records in SNARS Edition 1.